Clostridium difficile-associated disease in versatile hospital patient population and risk factors for its development - Ya. N. Yarushina; G. B. Kolotova; V. A. Rudnov; V. A. Bagin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate proportion of patients with Clostridium difficile-associated disease in the spectrum of patients of versatile hospital and reveal its risk factors. Material and methods. Retrospective analysis of 131 case records of the in-patients of Yekaterinburg City Hospital No. 40 for the year 2014 who developed diarrhea during antibacterial therapy was carried out. According to fecal filtrate test for Clostridium difficile (CD), patients were divided into two groups: 71 patients had positive test, 60 - negative. Results. Proportion of patients with C. difficile-associated disease in Yekaterinburg City Hospital No. 40 for the year 2014 was 0,14% of total in-patient number. Predictors of C. difficile-associated diarrhea risk were following: the age over 65 years (OR=3.43; 95%CI 1.06-11.08; р=0.0409), Charlson comorbidity index over 2 points (OR=2,92, 95%CI 1.33-6.44; р=0.0114), presence of anemia (OR=4,35, 95%CI 1.98-9.54; р=0.0003), admission to intensive care unit with staying for more than 1 day (OR=10.59; 95%CI 2.35-47.69; р=0.0002) and in surgical departments (OR=2.46; 95%CI 1.16-5.20; р=0.0276), surgical intervention (OR=3.06; 95%CI 1.33-7.04; р=0.0120), hospital stay for 5 days (OR=3.87; 95%CI 1.87-8.01; р=0.0004), chronic dialysis at chronic renal failure (OR=8.56; 95% of CI 1,05-69,69; р=0,0210), installation of an urethral catheter (OR=3,43; 95% of CI 1.06-11.08; р=0.0409), proton pump inhibitors (PPI) therapy for over 7 days (OR=7.76; 95% CI 1.69-35.53; р=0.0032), antibacterial therapy for over 5 days (OR=4.10; 95%CI 1.93-8.68; р=0.0003), more than one course} of antibacterial treatment (OR=5.31; 95% CI 1.12-25.03; р=0.0365), ceftriaxone therapy (OR=3.21; 95%CI 1.51-6.82; р=0.0036). Conclusions. Following risk factors for C. difficile-associated diarrhea were determined: age over 65 years, presence of several associated diseases (Charlson score >2), chronic renal failure that require hemodialysis, anemia, admission to intensive care unit and surgical departments, surgical treatment, PPI administration for over 7 days, more than one course of antibiotic treatment and duration of antibacterial therapy for more than 5 days, administration of 3rd generation cephalosporins.